2022
DOI: 10.1016/j.toxrep.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of sub-lethal acute toxicity of Emamectin benzoate in Labeo rohita using multiple biomarker approach

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 56 publications
(102 reference statements)
4
6
0
Order By: Relevance
“…Emamectin benzoate (EMB) is a macrocyclic lactone agrochemical obtained from the natural fermentation of the soil‐dwelling actinomycetes 2 . EMB could be wildly used as insecticides, acaricides or bactericides in agriculture and veterinary medicine with high bioactivity and broad spectrum 3 . The total amount of EMB used is the fastest growing among natural product pesticides from 2007 to 2012 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emamectin benzoate (EMB) is a macrocyclic lactone agrochemical obtained from the natural fermentation of the soil‐dwelling actinomycetes 2 . EMB could be wildly used as insecticides, acaricides or bactericides in agriculture and veterinary medicine with high bioactivity and broad spectrum 3 . The total amount of EMB used is the fastest growing among natural product pesticides from 2007 to 2012 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 EMB could be wildly used as insecticides, acaricides or bactericides in agriculture and veterinary medicine with high bioactivity and broad spectrum. 3 The total amount of EMB used is the fastest growing among natural product pesticides from 2007 to 2012. 4 EMB could spread into the environment in the form of binding to soils or sediment and have a long degradation with a half-life time of over 120 days.…”
Section: Introductionmentioning
confidence: 99%
“…Clarias gariepinus juveniles are highly sensitive to Ivermectin, with a LC50 of 15 µg/L under static conditions [13]. Studies found that Emamectin benzoate altered the blood factors in Labeo rohita [14], in Oreochromis niloticus [15] and in C. gariepinus [13].…”
Section: Experimental Designmentioning
confidence: 99%
“…It is adjusted to laboratory conditions easily. Many studies have been done to investigate the changes in the hematology of Labeo rohita treated with emamectin benzoate [17].…”
Section: Introductionmentioning
confidence: 99%